Analisis Perubahan Strategi Pemasaran Buku Anak Islami pada UMKM CV Gulali Edukasi Indonesia Periode 2018-2023 - Muldani Badrianto; Dedy Rachmad (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2024)
This research analyzes the marketing strategy changes implemented by CV Gulali Edukasi Indonesia, an MSME, in marketing Islamic children's books during the period of 2018-2023. The study aims to understand the transition from traditional marketing strategies, relying on resellers, to digital marketing based on e-commerce and social media. This study uses qualitative and quantitative methods with a descriptive case study approach at CV Gulali Edukasi Indonesia during the 2018-2023 period. The findings reveal that the digital marketing strategy through marketplaces like Shopee significantly boosted sales, especially in 2023. However, there was a sharp decline in the B2B distribution channel due to a failure in product absorption by partners and the closure of Togamas bookstores. The implementation of sharia marketing principles, such as honesty and social responsibility, helped strengthen the company's relationships with consumers and business partners. Additionally, the company began exploring international expansion into Muslim-majority countries such as Malaysia, Singapore, and the United Arab Emirates. In conclusion, despite challenges in distribution, effective digital marketing strategies and a commitment to sharia principles provide strong growth potential for the business in both domestic and international markets.